Library Metadata Standards and Linked Data Services: An Introduction to Arab and International Organizations. Issue 3 (8th October 2019) - Eid, Sherine
Abstract: This article aims to give an overview of Arab and international organizations that promulgate library metadata standards and linked data services—ranging from those whose sole purpose is the setting of standards and linked data technology, to those that develop standards and provide linked data as subsidiary services.